Effect of mat anchorage on flexural bonding strength between concrete and sand coated GFRP bars. (1st October 2021) - Shakiba, Milad; Oskouei, Asghar Vatani; Karamloo, Mohammad; Doostmohamadi, Alireza
Abstract: In the present study, the impacts of using six different configurations of handmade mat anchorages on the improvement of bonding between normal concrete and GFRP bars have been investigated. To do so, 63 beam specimens of three different concrete mixes were cast. The beams were cast in accordance with RILEM recommendations and all tests were conducted under the same condition. The results indicated that the use of anchorage system could substantially enhance the bond between concrete and GFRP bars. However, the increase of both diameter and length of the anchorage did not significantly affect the bonding between concrete and GFRP bars. In addition, test results showed that the increase of anchorage number did not enhance the bond behavior of the anchorage system. Indeed, as the concrete compressive strength increased, the developed stress in GFRP bars increased. Moreover, the results have been compared with the empirical relations proposed by international codes and guidelines. The comparison showed that the suggested empirical relations by American Concrete Institute, Canadian Standard Association, Canadian Highway Bridge Design Code and Japan Society of Civil Engineers for the development length yield quite conservative results.